BCL2L12 improves risk stratification and prediction of BFM-chemotherapy response in childhood acute lymphoblastic leukemia - Avgeris, M.; Stamati, L.; Kontos, C.K.; Piatopoulou, D.; Marmarinos, A.; Xagorari, M.; Baka, M.; Doganis, D.; Anastasiou, T.; Kosmidis, H.; Gourgiotis, D.; Scorilas, A. (Clin Chem Lab Med, 2018)
Background Risk-adjusted treatment has led to outstanding improvements of the remission and survival rates of childhood acute lymphoblastic leukemia (ALL). Nevertheless, overtreatment-related toxicity and resistance to therapy have not been fully prevented. In the present study, we evaluated for the first time the clinical impact of the apoptosis-related BCL2L12 gene in prognosis and risk stratification of BFM-treated childhood ALL. Methods Bone marrow specimens were obtained from childhood ALL patients upon disease diagnosis and the end-of-induction (EoI; day 33) of the BFM protocol, as well as from control children. Following total RNA extraction and reverse transcription, BCL2L12 expression levels were determined by qPCR. Patients' cytogenetics, immunophenotyping and minimal residual disease (MRD) evaluation were performed according to the international guidelines. Results BCL2L12 expression was significantly increased in childhood ALL and correlated with higher BCL2/BAX expression ratio and favorable disease markers. More importantly, BCL2L12 expression was associated with disease remission, while the reduced BCL2L12 expression was able to predict patients' poor response to BFM therapy, in terms of M2-M3 response and MRD>/=0.1% on day 15. The survival analysis confirmed the significantly higher risk of the BFM-treated patients underexpressing BCL2L12 at disease diagnosis for early relapse and worse survival. Lastly, evaluation of BCL2L12 expression clearly strengthened the prognostic value of the established disease prognostic markers, leading to superior prediction of patients' outcome and improved specificity of BFM risk stratification. Conclusions The expression levels of the apoptosis-related BCL2L12 predict response to treatment and survival outcome of childhood ALL patients receiving BFM chemotherapy.
Keywords: *Apoptosis; *Bcl2; *BCL2-like 12; *Berlin-Frankfurt-Munster; *biomarker; *cancer marker; *childhood ALL; *hematological cancer; *pediatric cancer; *tumor marker; Antineoplastic Combined Chemotherapy Protocols/*pharmacology; Apoptosis/drug effects; Child; Child, Preschool; Female; Humans; Immunophenotyping; Infant; Male; Muscle Proteins/*genetics/immunology; Neoplasm, Residual; polymerase chain reaction; Precursor Cell Lymphoblastic Leukemia-Lymphoma/diagnosis/*drug therapy/genetics; Proto-Oncogene Proteins c-bcl-2/*genetics/immunology; Risk Factors; RNA, Neoplasm/genetics/immunology/isolation & purification